The ​ ​representation ​ ​of ​ ​refuge ​ ​and ​ ​migration ​ ​in ​ ​the ​ ​online ​ ​media ​ ​in ​ ​Brazil ​ ​and abroad: ​ ​a ​ ​Cognitive ​ ​Linguistics ​ ​analysis - Ferreira, Luciane C; Flister, Catarina Valle; Morosini, Cassio (Signo, 2017)
The present study aims at mapping how the situation of refuge and migration is representedmetaphorically in the Brazilian online media. From the data collected, we will establishcomparisons between the representations that were found. An approach that contemplates theframe study employed in the media allows us to observe that verbal and nonverbal resources,metaphorical sentences and lexical items are constituted into discursive ​frames. ​We intend todiscuss how the migrant and the refugee are represented in the Brazilian online media. Somequestions we will investigate are: What are the discourses on the reception of refugees andmigrants? Which discourses on the integration of refugees and migrants are broadcasted? Fromthese questions, we will examine how such categories compose the image of the migrant and therefugee. The corpus used was based on the news of the online newspaper ​Folha de São Paulofrom June, 2015, seen as it was in this month that the so called “refugee crisis” occurred inEurope. The gathering and analysis were done with the help of two free softwares: Notepad++,that allows the user to save texts in ​txt format, and Antconc, that enables the analysis of severaltxt files through tools that are used in Corpus Linguistics. The concordance lines obtained byinserting a word of choice in AntConc’s concordancer were then analyzed manually throughCameron’s (2010) Metaphor-led Discourse Analysis. A larger objective will be to identify whichmetaphorical ​frames are used in the migrant’s and refugee’s media representation and what aretheir social implications. Such frames contribute to organize and potentialize the discourse aboutthe ​ ​Other ​ ​(BRUNO, ​ ​2016).